1999
DOI: 10.1046/j.1365-2265.1999.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of endurance training‐induced changes on glucocorticoid sensitivity of monocytes by an acute exercise

Abstract: We demonstrate in vitro plasticity of monocyte glucocorticoid sensitivity of endurance trained men, with training-induced decreased glucocorticoid sensitivity and acute exercise-induced return to the levels of the control untrained men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
3
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 26 publications
4
23
3
2
Order By: Relevance
“…Lastly, differences in glucocorticoid sensitivity are probably not restricted to the pituitary, as we have recently demonstrated that in vitro sensitivity of monocytes to dexamethasone is reduced in ET compared with sedentary men (24). These modifications, within limits, may prove adaptive and protective against prolonged exercise-induced cortisol secretion.…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, differences in glucocorticoid sensitivity are probably not restricted to the pituitary, as we have recently demonstrated that in vitro sensitivity of monocytes to dexamethasone is reduced in ET compared with sedentary men (24). These modifications, within limits, may prove adaptive and protective against prolonged exercise-induced cortisol secretion.…”
Section: Discussionmentioning
confidence: 98%
“…The changes in scores on Social Stress (r ¼ 70.7; P 5 0.001) and Lack of Energy (r ¼ 70.65; P 5 0.01) were related to changes in the DHEA-S/ C ratio, and the changes in scores on Physical Complaints were related to changes in cortisol concentrations as a result of rapidly increased training load. During training, activation of the hypothalamo-pituitary-adrenal (HPA) axis represents a physiological response to the strain of muscle exercise explaining increased cortisol concentrations (Duclos et al, 1999). Changes in cortisol concentrations reflect the metabolic stress as the endpoint of the HPA ( Jü rimäe et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HPA adaptation to normal training is characterised by increased ACTH/cortisol ratio only during exercise recovery (due to decreased pituitary sensitivity to cortisol) (Lehmann et al 1993b;Duclos et al 1997Duclos et al , 1998, and by modulation REVISION : Consensus Statement "Overtraining" (17-07-2012) 10 of tissue sensitivity to glucocorticoids (Duclos et al 1999(Duclos et al , 2003). However, it should be emphasized that during a resting day, in endurance-trained athletes 24 h cortisol secretion under non-exercising conditions is normal Duclos et al 1999Duclos et al , 2003. Accordingly, morning plasma cortisol concentration and 24 h urinary free cortisol (UFC) excretion in resting endurance-trained men are similar to those of age-matched sedentary subjects (Kern et al 1995;Duclos et al 1997;Gouarne et al 2005).…”
Section: Biochemistry and Hormones Biochemistrymentioning
confidence: 99%